Featuring Software Defined Radio in Airports for Finding Automatic Descendants Surveillance - Arief Epti Nur Putra, Ardian; Pamungkas, Wahyu; Wicaksono, Agung (Universitas Syiah Kuala, 2025)
As air traffic becomes more complicated, more effective monitoring systems are required to assure aviation safety and security. Automatic Dependent Surveillance-Broadcast (ADS-B) technology has become the international standard for real-time airplane tracking, however typical ADS-B receivers used in airports are expensive and frequently unavailable. This study seeks to assess the dependability and efficiency of Software Defined Radio (RTL-SDR) as a low-cost option for receiving ADS-B signals. The study focuses on the development of a 1090 MHz PCB antenna coupled to an RTL-SDR device, with data processed using RTL1090 software and visualized using Virtual Radar Server. Testing took place at two airports: Yogyakarta International Airport (YIA) and Wirasaba Airport. The results show that the system can identify aircraft within a range of up to 400 km at YIA and 250 km at Wirasaba, with the received data providing precise information on aircraft position, altitude, and speed. The system spotted four airplanes in Wirasaba and nine at YIA, indicating that the latter location has broader coverage. These findings show that RTL-SDR is a dependable and cost-effective option for ADS-B signal reception, with the potential to replace more expensive conventional receivers used in airports.